Posterior Reversible Encephalopathy Syndrome and Pregnancy: Case Report - Fernández, María Ximena (2015)
Posterior Reversible Encephalopathy Syndrome (PRES) is a clinical and radiological condition given by neurologic signs along with characteristic imaging findings. During pregnancy, its presentation is associated to Eclampsia. We present the case of an 18-year-old patient who develops treatment refractory eclampsia and HELLP syndrome during immediate puerperium, thus leading to the diagnosis of PRES and referral to intensive care. Imaging assessment confirmed diagnosis, with successful results. PRES consists of a heterogeneous group of pathologic processes, triggered by multiple etiologies, in our case secondary to hypertensive encephalopathy caused by Preeclampsia-Eclampsia Syndrome. Association of PRES, Preeclampsia-Eclampsia Syndromeand HELLP such as the case of our patient, is extremely rare with limited amount of case reports.